Primary mesenteric extraskeletal osteosarcoma - Ahmed, S. A.; Mohammed, U.; Garba, E. S.; Calvin, B.; Shehu, M. S. (Nigerian Journal of Basic and Clinical Sciences, 2026)
Extraskeletal osteosarcoma (EOS) is a rare malignant soft tissue tumor. It predominantly occurs in the extremities, and is highly aggressive and rarely involves the visceral organs. Only five cases of mesenteric EOS have been reported in English literature. We describe a male patient of 56 years, who was diagnosed to have EOS arising from small bowel mesentery. Literature search and review was made. This patient presented with lower gastrointestinal bleeding. Resection of the tumor with adjacent small bowel was performed. Histopathology was performed and it revealed an osteosarcoma of mesentery. Given the rarity of cases of mesenteric EOS, its biologic behavior at this location remains to be determined. There should be high index of suspicion because of the possible fatal outcome related to the tumor. EOS has a very poor prognosis and a promising therapeutic regimen does not exist.
Keywords: Extraosseous; mesenteric; mesentery; osteogenic sarcoma